2023
DOI: 10.4239/wjd.v14.i1.1
|View full text |Cite
|
Sign up to set email alerts
|

Current scenario of traditional medicines in management of diabetic foot ulcers: A review

Abstract: Diabetic foot infections and diabetic foot ulcers (DFU) cause significant suffering and are often recurring. DFU have three important pathogenic factors, namely, microangiopathy causing local tissue anoxia, neuropathy making the foot prone to injuries from trivial trauma, and local tissue hyperglycaemia favouring infection and delaying the wound healing. DFU have been the leading cause for non-traumatic amputations of part or whole of the limb. Western medicines focus mainly on euglycaemia, antimicrobials, deb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 112 publications
0
1
0
1
Order By: Relevance
“…complete ulcer healing rate was significantly higher in the total cast offloading group compared to the ordinary dressing group. This finding aligns with the results from Armstrong et al, who reported superior outcomes with offloading devices in managing plantar diabetic foot ulcers compared to non-offloading methods Rayate AS et al(2023)[7]. The higher effectiveness of total cast offloading is likely due to the reduction of pressure at the ulcer site, which is crucial for healingKhan MS et al(2023)[8].…”
supporting
confidence: 79%
“…complete ulcer healing rate was significantly higher in the total cast offloading group compared to the ordinary dressing group. This finding aligns with the results from Armstrong et al, who reported superior outcomes with offloading devices in managing plantar diabetic foot ulcers compared to non-offloading methods Rayate AS et al(2023)[7]. The higher effectiveness of total cast offloading is likely due to the reduction of pressure at the ulcer site, which is crucial for healingKhan MS et al(2023)[8].…”
supporting
confidence: 79%
“…The primary treatment comprises of topical dressings, an ideal dressing material should promote reepithelization, maintain moisture environment, possess antimicrobial properties, prevent further trauma and absorb exudates. As the available dressing options have limitations, none seem sufficient to ensure a successful, complete, non-recurring healing and are often possess costly affairs (10,11,12). Traditional medicines may be used in overcoming these difficulties.…”
Section: Discussionmentioning
confidence: 99%
“…The medicinal properties of these ingredients described in the text Agathiyar Gunavagadam also supports its wound healing properties (8,13). Sesame oil is rich in biologically active components such as linoleic acid, linolenic acids, lignans such as sesamin, sesamolin, and sesaminol, natural vitamin E, and phytosterols (12,14). Semecarpus a n a c a rd i u m L i n n .…”
Section: Discussionmentioning
confidence: 99%
“…Saat ini telah terjadi peningkatan yang signifikan dalam mengeksplorasi obat alternatif yang berasal dari sumber daya alam, terutama tanaman obat dengan tujuan pencegahan dan pengobatan kondisi kaki diabetik. Mengobati kaki diabetik dengan pengobatan tradisional sering dilakukan terutama di negara-negara miskin karena biaya yang lebih murah, efek samping kecil, dan kurangnya akses ke dokter bedah vaskular (Rayate, Nagoba, Mumbre, Mavani, Gavkare, & Deshpande, 2023). Berbagai produk herbal topikal digunakan untuk menyembuhkan kaki diabetik, dan banyak penelitian telah menyelidiki apakah efisiensi serta efektivitasnya dalam penyembuhan UKD (Bekele, Berhanu, Sefera, & Babu, 2022;Ansari, Akther, Khan, Islam, Masud, Rahman, & Abdel-Wahab, 2022).…”
Section: Pendahuluanunclassified